Central Bank Transparency and Cross-border Banking - Stefan Eichler; Helge Littke; Lena Tonzer (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2016)
We analyze the effect of central bank transparency on cross-border bank activities. Based on a panel gravity model for cross-border bank claims for 21 home and 47 destination countries from 1998 to 2010, we find strong empirical evidence that a rise in central bank transparency in the destination country, on average, increases cross-border claims. Using interaction models, we find that the positive effect of central bank transparency on cross-border claims is only significant if the central bank is politically independent. Central bank transparency and credibility are thus considered complements by banks investing abroad.
urn:nbn:de:gbv:3:2-54634
Keywords: E58; F30; G15; 330; central bank transparency; cross-border banking; gravity model